Reciprocal prediction of medication adherence and neurocognition in HIV/AIDS [Image: see text] - Ettenhofer, Mark L. (American Academy of Neurology, 2010)
BACKGROUND: Antiretroviral medications have been shown to benefit neurocognition in HIV/AIDS, and neurocognitive deficits are a risk factor for poor adherence to these medications. However, little is known about the predictive pathways linking medication adherence with cognitive ability. METHODS: In the current 6-month cohort study, antiretroviral medication adherence was tracked prospectively among 91 HIV-positive adults using electronic monitoring. Comprehensive neuropsychological evaluations were performed at baseline and 6 months. RESULTS: Multivariate path analyses provided evidence that antiretroviral adherence and cognitive ability are reciprocally related, although the neurocognitive pathways of this relationship appear to vary by predictive direction. Executive function and learning/memory were most strongly predictive of levels of medication adherence achieved, whereas higher levels of adherence were predictive of relative improvements in a wide range of frontostriatal brain functions including processing speed, attention, executive functions, and motor functioning. CONCLUSIONS: These data provide evidence that cognition and adherence are reciprocally related in HIV/AIDS. In particular, executive dysfunction may play a key role in this relationship. Interventions aimed at improving or preserving executive functions could hold promise for interrupting progressive declines in adherence and neurocognitive ability in HIV/AIDS. GLOSSARY: DSM-IV: = Diagnostic and Statistical Manual of Mental Disorders, 4th edition; HAART: = highly active antiretroviral therapy; MEMS: = Medication Event Monitoring System; PI: = protease inhibitor.